ZnAs@SiO(2) nanoparticles as a potential anti-tumor drug for targeting stemness and epithelial-mesenchymal transition in hepatocellular carcinoma via SHP-1/JAK2/STAT3 signaling - Huang, Yongquan (Theranostics, 2019)
Rationale: Current therapies for hepatocellular carcinoma (HCC) are hampered by treatment failure and recurrence due to the remaining treatment-resistant liver cancer stem cells (CSCs). Stemness and epithelial-mesenchymal transition (EMT) are regarded as two fundamental characteristics of liver CSCs necessary for cancer progression; thus, drugs that simultaneously target both characteristics should prove effective in eliminating HCC and impeding recurrence. In this study, we developed new arsenic trioxide (ATO)-based nanoparticles (NPs), which are expected to be more effective than the current HCC therapy, and explored their potential mechanism. Methods: A “one-pot” reverse emulsification approach was employed to prepare the ZnAs@SiO(2) NPs. HCC cell lines, MHCC97L and Hep3b, were used to analyze the antitumor activity of ZnAs@SiO(2) NPs in vitro and in vivo by quantifying cell growth and metastasis as well as to study the effect on stemness and EMT. SHP-1 siRNA was used to validate the role of the SHP-1/JAK2/STAT3 signaling pathway in mediating inhibition of stemness and EMT by ZnAs@SiO(2). Results: Compared with the current ATO treatment, ZnAs@SiO(2) NPs promoted apoptosis and significantly inhibited proliferation, migration, and invasion of both MHCC97L and Hep3b cells. In the in vivo assay, ZnAs@SiO(2) NPs inhibited tumor growth by 2.2-fold and metastasis by 3.5-fold as compared to ATO. The ZnAs@SiO(2) NPs also inhibited tumor spheroid formation in vitro and tumor initiation in vivo and induced significant changes in the expression of stemness markers (CD133, Sox-2, and Oct-4) and EMT markers (E-cadherin, Vimentin, and Slug) both in vitro and in vivo. These effects of ZnAs@SiO(2) that correlated with prognosis of HCC were mediated by the SHP-1/JAK2/STAT3 signaling. Conclusions: ZnAs@SiO(2) NPs can effectively suppress tumor initiation, growth, metastasis, and inhibit stemness and EMT through regulation of SHP-1/JAK2/STAT3 signaling pathway in liver cancer cells in vitro and in vivo. Thus, ZnAs@SiO(2) NPs have immense potential for HCC treatment in the future.